2014
DOI: 10.1152/ajprenal.00499.2013
|View full text |Cite
|
Sign up to set email alerts
|

Kindlin-2 regulates renal tubular cell plasticity by activation of Ras and its downstream signaling

Abstract: regulates renal tubular cell plasticity by activation of Ras and its downstream signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 54 publications
(56 reference statements)
1
22
0
1
Order By: Relevance
“…We also proved that activated Ras can markedly rescue RNA Pol I activity during defective integrin signaling, demonstrating the critical role of Ras in the whole process. There is a previous report demonstrating that kindlin-2 promotes Ras activation and its downstream signaling (34). Our study confirms the critical role of Ras in kindlin-2 signaling.…”
Section: Discussionsupporting
confidence: 90%
“…We also proved that activated Ras can markedly rescue RNA Pol I activity during defective integrin signaling, demonstrating the critical role of Ras in the whole process. There is a previous report demonstrating that kindlin-2 promotes Ras activation and its downstream signaling (34). Our study confirms the critical role of Ras in kindlin-2 signaling.…”
Section: Discussionsupporting
confidence: 90%
“…We have already reported that H-Ras isoform is able to modulate renal fibrosis and myofibroblast activation following ureteral obstruction in mice [24, 27]. Notably Ras activation has been shown to be involved in EMT of tubular cells to myofibroblasts [49], and specifically H-Ras is involved in TGF- β 1-induced EMT [50]. In the kidney, chaetomellic acid A selectively inhibits the membrane-bound of H-Ras without affecting the membrane-bound of Ki-Ras or other prenylated intracellular proteins like Rab [51].…”
Section: Discussionmentioning
confidence: 99%
“…In affected mouse and human tubular epithelial cells, kindlin-2 is highly expressed and promotes EMT by increasing Erk1/2, Akt and TGFβ signaling. It has been demonstrated that kindlin-2 induces Ras activation through the recruitment of Son of sevenless homolog 1 (Sos1), which, subsequently, activates Erk1/2 and Akt signaling (Wei et al, 2014). Furthermore, kindlin-2 has been shown to activate the TGFβ signaling pathway through direct binding of its C-terminal FERM domain to transforming growth factor β receptor I (TβRI; also known as TGFBR1) and of its N-terminus to Smad3 (Wei et al, 2013).…”
Section: Kindlin-2 Is Involved In Multiple Diseasesmentioning
confidence: 99%